Uso de materiais refletivos e de práticas de manejo sobre a qualidade da uva merlot - Cabral, Vagner Bandeira (2011)
There are several types of cultural practices adopted on the grape plant orchard to improve fruit quality. However, this cultural practices demand for labor, which does not encourage farmers to adopt them. However, it is necessary to adopt practices that can produce quality fruits without increased demand for labor. The aim of this work was to evaluate the reflective film use and cultural practices in the pathology, physical-chemical, biochemical quality and physiologic Merlot grape. The experimental design was in blocks completely randomized, in factorial 3 x 2 (material type x cultural practices), with four replications, considering four plants by plot. The cultural practices factor was divided in two levels, with and without it. In the material type factor were tested two reflective film in the soil, white raffia plastic (polypropylene) (reflective film 1) and metalized raffia plastic (reflective film 2). The pathology, physical-chemical and biochemical quality characteristics were evaluated in harvest fruit moment. The physiologic plants aspects and microbiological soil activity were evaluated, too. The reflective material use in the soil reduced fruit lost, what it increase the yield per plant. Cultural practices had no influence on the organoleptic and biochemical grape characteristics, it providing only a greater number of berries per cluster. The use of reflective films showed higher microbial activity in soil.